2022
DOI: 10.3390/vaccines10020236
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2–Specific Vaccine Candidates; the Contribution of Structural Vaccinology

Abstract: SARS-CoV-2 vaccine production has taken us by storm. We aim to fill in the history of concepts and the work of pioneers and provide a framework of strategies employing structural vaccinology. Cryo-electron microscopy became crucial in providing three-dimensional (3D) structures and creating candidates eliciting T and B cell-mediated immunity. It also determined structural changes in the emerging mutants in order to design new constructs that can be easily, quickly and safely added to the vaccines. The full-len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 94 publications
0
14
0
Order By: Relevance
“…Current vaccines have been shown to induce highly effective CD8 + T cell responses, but generally only exploit the S protein. 51 This means that vaccine‐induced CD8 + T cells target a narrow range of spike‐derived epitopes. The current study identified 10 spike‐derived epitopes across eight HLA‐I allotypes, of which A*02:01/s 269–277 , A*03:01/S 378–386 and A*24:02/S 1208–1216 are the only epitopes that induced high CD8 + T cell frequencies in the majority of convalescent donors expressing the respective HLA‐I allotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current vaccines have been shown to induce highly effective CD8 + T cell responses, but generally only exploit the S protein. 51 This means that vaccine‐induced CD8 + T cells target a narrow range of spike‐derived epitopes. The current study identified 10 spike‐derived epitopes across eight HLA‐I allotypes, of which A*02:01/s 269–277 , A*03:01/S 378–386 and A*24:02/S 1208–1216 are the only epitopes that induced high CD8 + T cell frequencies in the majority of convalescent donors expressing the respective HLA‐I allotype.…”
Section: Discussionmentioning
confidence: 99%
“…Vaccination is the most effective way to protect against (severe) COVID‐19. Current vaccines have been shown to induce highly effective CD8 + T cell responses, but generally only exploit the S protein 51 . This means that vaccine‐induced CD8 + T cells target a narrow range of spike‐derived epitopes.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the approved anti-COVID-19 front-line vaccines based on expressible embedded mRNA and replicationincompetent adenovirus vectors [118,231,232], a recombinant vaccine has come to market (Table 1, [157]) and other many alternative recombinant vaccines are also approached through under fast developing strategies. Because of the broad clinical experience in protein-based vaccination, such protein-based vaccines are expected to enter the prophylaxis landscape and complement or even substitute, in the longer term, the nucleic acid versions [233][234][235][236]. Due to the enormous investment in testing immunization strategies against SARS-CoV-2 infection, a comprehensive and updated overview of the spectrum of vaccine prototypes is just not feasible and it is beyond the scope of this review.…”
Section: Recombinant Vaccines For Covid-19mentioning
confidence: 99%
“…The entire S protein (BNT162b2/COMIRNATY Tozinameran (INN) (Pfizer, USA (BNT162b2)); NVX-CoV2373/Covovax/Nuvaxovid/Novavax (Novavax, India (NVX-CoV2373)); MVC-COV1901 (Medigen, Germany (MVC-COV1901)); mRNA-1273/Spikevax (Moderna, USA (mRNA-1273)); and EpiVacCorona (Vector State Research Center of Virology and Biotechnology, Russia)), its receptor-binding domain (RBD) (Abdala, CIGB, Cuba (Abdala)), which is responsible for the binding of the virus to the angiotensin-converting enzyme 2 (ACE) receptor, and the N-terminal domain (NTD) are primarily used in the development of COVID-19 vaccines [ 14 , 15 ].…”
Section: Covid-19 Vaccine Platforms and Their Characteristicsmentioning
confidence: 99%